35. THE MANAGEMENT COMPETENCY AMONG HEADNURSES AT HOSPITALS AND HEALTH CENTERS WITH INPATIENT BEDS IN TUYEN QUANG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the current status of management capacity of headnurses at hospitals and medical centers with beds in Tuyen Quang province and propose solutions to improve the management capacity of headnurses in medical facilities in the province.Method: A cross-sectional descriptive method using quantitative research with 14 hospital head nurses, 89 head nurses and 618 nurses at 14 hospitals and medical centers with inpatient beds in Tuyen Quang province from April to May 2024.Results: The current capacity of head nurses was still limited. The average score of all 5 capacity groups ranged from 3 to 3.85 points. Currently, the professional management capacity group of head nurses was assessed to be the best and the weakest capacity is financial management capacity. In each group of management competencies, there were many criteria that were still very limited and a need for training to improve capacity in the coming time.Conclusion: The average scores of the head nurses in all 5 skill groups are quite low. Currently, the best ability is professional ability and the weakest is financial management ability.
Keywords: Management capacity; head nurses; hospital.